IMPLEMENTASI PROGRAM SEKOLAH PENGGERAK DAN PERAN GURU PENGGERAK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMA NEGERI 9 MAKASSAR - Ahmad Restani (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This study aims to analyze the implementation of the Driving School Program (Program Sekolah Penggerak) and the role of Driving Teachers (Guru Penggerak) in improving the quality of learning at SMA Negeri 9 Makassar. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving the principal, Driving Teachers, teachers, and students as research informants. The results showed that the implementation of the Driving School Program brought positive changes to the learning process through student-centered learning, differentiated instruction, technology integration, and the strengthening of the Pancasila Student Profile. Driving Teachers played important roles as instructional leaders, facilitators, motivators, and agents of change in improving the quality of learning at school. The program also had positive impacts on students’ learning motivation, participation, creativity, and character development. However, several challenges were still found, such as teachers’ adaptation to the flexible curriculum and the use of technology in learning. Therefore, strengthening teacher competence and providing continuous assistance are necessary to optimize the implementation of the Driving School Program.